Hspa13 Promotes Plasma Cell Production and Antibody Secretion - He, Youdi; Xu, Ruonan; Zhai, Bing; Fang, Ying; Hou, Chunmei; Xing, Chen; Xiao, He; Chen, Guojiang; Wang, Xiaoqian; Ma, Ning; Han, Gencheng; Wang, Renxi (Frontiers in Immunology, 2020)
The generation of large numbers of plasma cells (PCs) is a main factor in systemic lupus erythematosus (SLE). We hypothesize that Hspa13, a member of the heat shock protein family, plays a critical role in the control of PC differentiation. To test the hypothesis, we used lipopolysaccharide (LPS)-activated B cells and a newly established mouse line with a CD19cre-mediated, B cell–specific deletion of Hspa13: Hspa13 cKO mice. We found that Hspa13 mRNA was increased in PCs from atacicept-treated lupus-prone mice and in LPS-stimulated plasmablasts (PBs) and PCs. A critical finding was that PBs and PCs [but not naïve B cells and germinal center (GC) B cells] expressed high levels of Hspa13. In contrast, the Hspa13 cKO mice had a reduction in BPs, PCs, and antibodies induced in vitro by LPS and in vivo by sheep red blood cells (SRCs)- or 4-hydroxy-3-nitrophenylacetyl (NP)-immunization. Accordingly, the Hspa13 cKO mice had reduced class-switched and somatically hypermutated antibodies with defective affinity maturation. Our work also showed that Hspa13 interacts with proteins (e.g., Bcap31) in the endoplasmic reticulum (ER) to positively regulate protein transport from the ER to the cytosol. Importantly, Hspa13 mRNA was increased in B220+ cells from patients with multiple myeloma (MM) or SLE, whereas Hspa13 cKO led to reduced autoantibodies and proteinuria in both pristane-induced lupus and lupus-prone MRL/lpr mouse models. Collectively, our data suggest that Hspa13 is critical for PC development and may be a new target for eliminating pathologic PCs.